ANALISIS PENERAPAN ETIKA FOTO HUKUM CAMBUK DI SERAMBINEWS.COM PERIODE NOVEMBER DAN DESEMBER 2018 - Vinda Eka Saputra; Muzakkir Muzakkir; Putri Maulina (Universitas Teuku Umar, 2019)
This study aims to examine the ethics of whip law journalism in serambinews.com on November to December 2018. It uses the analysis of Charles Sanders Peirce's semiotic text with a qualitative approach. In this study, the researcher took three photos as objects to be studied. The data collection techniques used in this study are text observation method and documentation method. Based on the review of the Sign, Object and Interpretation of those three photos, it shows that thosephotos are not in accordance with the ethics of photojournalism. Some things are not in accordance with the ethics of photojournalism. It still clearly seeing the face of the perpetrators who were sentenced to caning without censorship which should be disguised or not shown clearly, either by blurring or taking photos from an angle that does not show the face of the perpetrator. Keywords: Ethics, Photojournalism, Whip Law, Serambinews.com.